Utilization of Google Drive Use Among Students of the Faculty of Economics, Wiralodra University, Indramayu - Riqqah Nur’Aisyah Zuhra; Nur Afifah; Nela Yulianti; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to determine the use of Google Drive among students of the Faculty of Economics, Wiralodra University, emphasizing technological skills, information management, and interaction in the context of education. This study uses a qualitative approach using observation, in-depth interviews, and content analysis through Google Forms. Google Drive is highlighted as a significant contributor to efficient document storage, collaboration, and file accessibility for students. These findings underline its role in enhancing interaction with faculty members and facilitating activity monitoring. In conclusion, the positive adoption of Google Drive is in line with the paradigm of technological development as a useful tool in human life.